Rancangan Bangun Prototipe Sistem Pengamanan Ganda Pada Sepeda Motor Menggunakan Fingerprint Dan Remote Control RF Berbasis Internet Of Thing (IOT) Menggunakan ESP8266 - Kanzul Fadlillah; Ipriadi; Anggi Hadi Wijaya (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
Dual security system on motorcycles using fingerprint sensors and RF remote control using ESP 8266 based on the Internet of Things (IoT) as an efficient motorcycle security tool that provides a sense of security for vehicle owners is needed because of the rampant motorcycle theft. This study uses the Research and Development or RnD method. The dual security system on motorcycles is controlled via a microcontroller. RF remote control to open the solenoid as a double lock, data is processed by Arduino Mega and activates the system in the circuit. To activate the motorcycle, select the password input on the matrix keypad or scan fingerprint, If there is an error in the input, the buzzer will sound as a warning alarm and send the location to Telegram. After testing, the results obtained from this test show that integration between RF remote control, fingerprint, and IoT using ESP 8266 can provide a higher level of security and efficiency in preventing motorbike theft. With this prototype, a more reliable and modern double safety system can be applied to motorbikes, reducing dependence on conventional safety systems which are more susceptible to security risks.